Regeneração natural e relações ambientais em área de controle de Bambusa tuldoides Munro. - Felker, Roselene Marostega (2018)
Bamboos can pose risks to environmental sustainability as they form densification and cause competition, in the search for resources, with native species. Faced with this problem, bamboo control techniques can be an important tool for the recovery of these areas. Thus, the present work had as objective to evaluate areas submitted to different bamboo controls, monitoring the mechanisms of regeneration and soil bioindicators. Two control treatments (mechanical and chemical) were applied and two control areas were maintained, one native forest and another bamboo forest (MN: Witness Mata Nativa, BT: Bambu Witness, BH: Chemical Treatment, BA: Mechanical Treatment) 2014. After the controls were applied, the regeneration, seed rain, seed banks, soil bioindicators and environmental variables were monitored in each of the control areas. Natural regeneration was evaluated using the class interval of 30 ≤ H≤130 cm, performed in 80 subplots of 1x1m in each area, in the years of 2015 and 2017. In BA, soil cover analysis and percentage of regrowth of bamboos were carried out, additionally. Regeneration was analyzed for diversity, richness, similarity and also related to environmental variables (soil chemical and physical properties and luminosity). The seed rain was evaluated in the period from August 2015 to July 2016, through 10 collectors of 1x1m in each area. Diversity, richness and floristic similarity indexes were calculated. The seeds were differentiated into morphospecies and classified as the dispersion form. For the seed bank, ten soil samples were collected per area in May 2015, taken to the greenhouse and evaluated the emergence, floristic composition, density, and similarity. The soil bioindicators were collected in two post control periods (May and October), through pitfall traps, with ten replicates for each control area, and arthropods were identified in taxonomic groups. The groups were counted and identified and analyzed for diversity, similarity and correlations with soil areas and properties. It was verified that the control treatments were efficient in the resumption of the succession, not presenting phytosanitary damages in the regeneration and bioindicators of the soil. However, greater impacts were observed in the mechanical treatment (BA), mainly in relation to the soil. It is hoped that from this work, bamboo control techniques can be improved in order to restore environmental sustainability in areas dominated by bamboo.